Integrated therapy for lumbar strain in young/ middle-aged patients - Parker, Grace; Taylor, Elijah (Cambridge Sport Science, 2025)
Objective, This study aims to investigate the long-term therapeutic effects of conventional medical techniques—muscle release therapy and Pilates exercise, as well as their combination, on lumbar muscle strain in middle-aged and young patients. Methods: A total of 100 patients aged 20–50 years who visited six hospitals in Nanjing for lumbar muscle strain were randomly assigned to four groups: muscle release therapy group (Group A), Pilates exercise group (Group B), combined muscle release therapy and Pilates exercise group (Group C), and conventional acupuncture and massage therapy group (Group D), with 25 cases in each group. Each intervention session lasted 60 minutes and was conducted three times per week. The intensity of lumbar pain and lumbar spine mobility were assessed before the intervention and at 3, 6, and 12months post-intervention. Results: After three months of treatment, patients in the combined muscle release therapy and Pilates exercise group (Group C) showed significant improvements in all indicators compared to before treatment (P<0.05). At six months, this group continued to show significantly better outcomes than the other groups. The muscle release group (Group A) and the conventional acupuncture and massage group (Group D) had similar results, which were better than those in the Pilates exercise group (Group B). At 12 months, the combined treatment group (Group C) still had significantly better outcomes than the other groups. The Pilates exercise group (Group B) had better outcomes than the muscle release group (Group A) and the conventional acupuncture and massage group (Group D), but the differences between Group B and the other groups were not significant. The indicators of the muscle release group (Group A) and the conventional acupuncture and massage group (Group D) were similar. Conclusion: The combination of muscle release therapy and Pilates exercise is the most effective treatment for lumbar muscle strain in middle-aged and young patients.